The Effect of Continuous Feedback on High Service Learning According to Wrist Joint Modeling for Junior Squash Players - Nouman Hadi Alkhazraji (Journal of Global Pharma Technology, 2018)
The research problem concentrated on lack of effectiveness learning for high serve skill of squash players. Plenty of technical mistakes in skill performing, lack of use of feedback and not specifying the appropriate time by the coach commensurate with stages of skill learning. Therefore, the researchers sought to emerged the ongoing feedback through the unites to learning the high serve skill of squash to increase the effectiveness of learning and accelerate it, and the continuous correction of mistakes in order to the learner can master the skill with the least numbers of mistakes. However, the aims of the research were to identify the effect of continuous feedback on learning the high serve skill of squash junior players and to identifying the superiority of the differences between the effects of continuous feedback in learning the two skills of high serve among squash junior players. However, the researchers used the experimental approach (Equal groups design) with pre and post-tests. The research population involved (22) squash junior players in the Babylon university. The researchers have been equalization a number of variables in the experimental and control groups which may impact on the results later. Nevertheless, the research results showed A positive effect of the using of continuous feedback units on learning and developing skillful performance for the high serve skill of squash junior players. In addition, the experimental group has improved as a result of the use effect of continuous feedback in learning the two skills of high serve among squash junior players comparing to the control group.Keywords: Continuous feedback, High serves wrist joint, Modeling and squash.